Translating selected contemporary short stories from Taiwan a problem-based approach - Nicdao, Jose Marcelino A. (2011)
This study explores a subjective poetics involved in translating seven Chinese contemporary short stories from Taiwan to English. Materials from both Western and Chinese translation theories were used to come up with solutions to problems encountered in translating the text.